Dating violence perpetration: Masculine ideology and masculine gender role stress as predictors - Hana Berliani Adiningsih; Cantyo Atindriyo Dannisworo; Mellia Christia (Universitas Ahmad Dahlan, 2020)
Dating violence is one of intimate partner violence cases in Indonesia. Thus far, the motives of dating violence perpetration by a male partner to their intimate partner have not been established. This study aimed to identify the role of masculine ideology and masculine gender role stress as predictors of dating violence. This study collected data from three hundred and ten male college students aged 18-25 who have been involved in a romantic relationship for at least a year. The respondents were assessed with several measurement tools: Masculine Role Norm Inventory-Short Form (MRNI-SF), Masculine Gender Role Stress-Abbreviated (MGRS-A), and the Revised Conflict Tactics Scale (CTS2). Data collected in this study was then analyzed using multiple regression analysis techniques. The findings show that masculine ideology significantly predicted dating violence, while masculine gender role stress did not predict dating violence. The present research adds to the understanding of the association between masculinity as a cognitive system and gender-related experience of distress to dating violence. Furthermore, masculine ideology can be useful to identify men who are likely to perpetrate dating violence towards their female partners.